Applying Item Response Theory to the OPD Structure Questionnaire: Identification of a Unidimensional Core Construct and Feasibility of Computer Adaptive Testing. Issue 5 (3rd September 2021) - Obbarius, Alexander; Ehrenthal, Johannes C.; Fischer, Felix; Liegl, Gregor; Obbarius, Nina; Sarrar, Lea; Rose, Matthias
Abstract: Recent developments in the dimensional assessment of personality functioning have made the implementation of latent measurement models increasingly attractive. In this study, we applied item response theory (IRT) to a well-established personality functioning instrument (the OPD Structure Questionnaire) to identify a unidimensional latent trait and to evaluate the feasibility of computer adaptive testing (CAT). We hypothesized that the use of IRT could reduce the test burden – compared to a fixed short form – while maintaining high precision over a wide range of the latent trait. The OPD-SQ was collected from 1235 patients in a psychosomatic clinic. IRT assumptions were fulfilled. A 9-factor model yielded sufficient fit and unidimensionality in exploratory factor analysis with bifactor rotation. Items were iteratively reduced, and a graded-response IRT model was fitted to the data. Simulations showed that a CAT with approximately 7 items was able to capture an OPD-SQ global severity score with an accuracy similar to that of a fixed 12-item short form. The final item bank and CAT yielded satisfactory content validity. Strong correlations with depression and anxiety replicated previous results on the OPD-SQ. We concluded that IRT applications could be useful to reduce the test burden of personality functioning instruments.